The Influence of Workload, Stress, and Motivation on the Performance of Ward Nurses in the Hospital - Beanal, Christanto Metusail; Sinlae, Arny Merlyani Kurnia; Pratiwi, Asmida Putri; Pramesti, Lady Aurellia (Eduvest - Journal of Universal Studies, 2025)
Nurse performance is an important element in determining the quality of health services in hospitals. This study analyzes the effect of workload, stress, and motivation on the performance of inpatient nurses in a private hospital in Kupang City. Using a cross-sectional design with 88 respondents selected by proportional random sampling, data were collected through an online questionnaire and analyzed using the Pearson correlation test. The results showed that the majority of respondents were aged 20-29 years (59.1%), female (87.5%), had a bachelor’s degree (73.9%), and had worked for 1-5 years or more than 5 years (36.4%). Workload (p=0.03), work stress (p=0.006), and work motivation (p<0.001) had a significant effect on nurse performance, with motivation being the most dominant factor. High motivation can improve nurse performance, even in the midst of workload and stress.